Aspirational Power : Brazil on the Long Road to Global Influence - Mares, David R.; Trinkunas, Harold A. (Book collections on Project MUSE., 2016)
"As the largest country in South America by land mass and population, Brazil has been marked since its independence by a belief that it has a potential to be more than merely a very large country. Set apart from the rest of the hemisphere by culture, language and history, Brazil has also been viewed by its neighbors as a potential great power, and at times, a threat. But even though domestic aspirations and foreign perceptions have held out the prospect for Brazil becoming a major power, the country has lacked the capabilities--particularly on the military and economic dimensions--to pursue a traditional path to greatness. Aspirational Power examines Brazil as a rising power. It explains Brazil's predilection for soft power through a historical analysis of Brazil's three previous attempts to achieve major power status, each of which shaped its present strategy. Though Brazil's efforts to rise have fallen short it will continue to try to overcome the obstacles to its rise, whether those obstacles are domestic or international"--